(untitled) (The Peerian Journal, 2023)
Tourism marketing is generally seen as the link between the needs and desires of tourists and the products of tourism facilities, It is constantly working on developing tourism offerings to meet the constant changes in the needs and desires of tourists, It also plays a leading and important role in increasing people’s desire for tourism which is the main driving force, On the other hand, the researcher wanted in his research tagged (strategic marketing performance and its impact on the quality of religious tourism service (A case study of the Arbaeen visitation service in the holy city of Kerbala)) to document the relationship between tourism marketing and religion through one of the most important Islamic events in the world which only happen once a year. The special interest of the researcher in the visitation Arbaeen service is the possibility of designing the service provided in a way that guarantees that the visitation Al Arbaeen becomes an enjoyable and safe experience for all comers from all over the world. For the purpose of covering what was mentioned, the structure of the research consisted of four sections. The first section reviewed the methodology of the research study, as it branched into five branches, which are the research problem, its hypothesis, its objective, its importance, methodology, and the research sample, in addition to the temporal and spatial limits, As for the second topic, it included the conceptual framework, where the topic centered on first: marketing strategic performance, secondly: the quality of religious tourism services, and thirdly: the forty visit and the mechanism of employing religious tourism marketing in providing high-quality service to visitors to the holy city of Kerbala, As for the third topic, it included the practical framework, which contained the results of the study sample responses according to their statistical analysis through the spss program, and also included a statement of the demographic information of the sample. Finally, the fourth topic, which included future results and recommendations related to subsequent studies of future topics related to the same content of the study.